Equilibrium between resources and expenditure of health sector of Social Security Fund: a case study of Iran - Ahmadi Dashtian, Azadeh; Mardali, Mohsen (Farmeconomia. Health economics and therapeutic pathways, 2017)
In Iran, Social Security is the most important institution of social insurance fund, currently insuring more than a half of country population, and it has a significant role in fulfilling short-term and long-term commitments. Therefore investigation of the balance of resources and expenditure of health sector of the fund can be a scientific process of the funding the future and can pave the way to provide necessary revisions in this sector. Analyzing equilibrium between resources and expenditure of health sector of Social Security Fund in the past years, the present study offers recommendations for improving it in terms of parametric and structural dimensions. The methodology includes documentary library methods and statistical part is descriptive using Excel. Findings indicated that, regarding the present lack of balance of resources and expenditure of health sector, keeping on with the present conditions can lead to many crises. As a result, to escape from the present conditions of the funds where lack of balance of resources and expenditure exists, carrying out parametric and management-structural revisions seems necessary.